NRG1 fusions in KRAS wild-type pancreatic cancer - Heining, Christoph; Horak, Peter; Richter, Daniela; Penzel, Roland; Endris, Volker; Ehrenberg, Karl Roland; Frank, Stephanie; Giese, Nathalia; Strobel, Oliver; Hackert, Thilo; Springfeld, Christoph; Bergmann, Frank; et al. (Cancer discovery, 2018)
We used whole-genome and transcriptome sequencing to identify clinically actionable genomic alterations in young adults with pancreatic ductal adenocarcinoma (PDAC). Molecular characterization of 17 PDAC patients enrolled in a precision oncology program revealed gene fusions amenable to pharmacologic inhibition by small-molecule tyrosine kinase inhibitors in all patients with KRAS wild-type (KRASwt) tumors (4 of 17). These alterations included recurrent NRG1 rearrangements predicted to drive PDAC development through aberrant ERBB receptor-mediated signaling, and pharmacologic ERBB inhibition resulted in clinical improvement and remission of liver metastases in two patients with NRG1-rearranged tumors that had proved resistant to standard treatment. Our findings demonstrate that systematic screening of KRASwt tumors for oncogenic fusion genes will substantially improve the therapeutic prospects for a sizeable fraction of PDAC patients.